Corrigendum to “Large sardine resource discovered off south-eastern Australia: Potential risks, challenges and benefits of establishing a new fishery” [Mar. Policy 155 (2023) 105739] - Tim M. Ward; Barrett W. Wolfe; Gretchen L. Grammer; Alex R. Ivey; Edward King; Andreas Schiller; Karlie S. McDonald; Jeffrey M. Dambacher (Marine Policy, 2025)

Large sardine resource discovered off south-eastern Australia: Potential risks, challenges and benefits of establishing a new fishery - Tim M. Ward; Barrett W. Wolfe; Gretchen L. Grammer; Alex R. Ivey; Edward King; Andreas Schiller; Karlie S. McDonald; Jeffrey M. Dambacher (Marine Policy, 2023)

Threat-abatement framework confirms habitat retention and invasive species management are critical to conserve Australia's threatened species - Stephen G. Kearney; James E.M. Watson; April E. Reside; Diana O. Fisher; Martine Maron; Tim S. Doherty; Sarah M. Legge; John C.Z. Woinarski; Stephen T. Garnett; Brendan A. Wintle; Euan G. Ritchie; Don A. Driscoll; et al. (Biological Conservation, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

What We Have Learned From the Framework for Ocean Observing: Evolution of the Global Ocean Observing System - Toste Tanhua; Andrea McCurdy; Albert Fischer; Ward Appeltans; Nicholas Bax; Kim Currie; Brad DeYoung; Daniel Dunn; Emma Heslop; Linda K. Glover; John Gunn; Katherine Hill; et al. (Frontiers in Marine Science, 2019)

Spawning patterns provide further evidence for multiple stocks of sardine ( Sardinops sagax ) off eastern Australia - Stuart C. Sexton; Tim M. Ward; John Stewart; Kerrie M. Swadling; Charlie Huveneers (Fisheries Oceanography, 2019)
Previous studies have suggested that sardine, Sardinops sagax , off eastern Australia spawns across its entire range when habitat conditions are suitable. However, recent studies have suggested that separate sub‐populations and spawning groups may occur in the region. Spawning patterns off eastern Australia were investigated using data collected during nine ichthyoplankton surveys conducted between 1997–2015, and adult reproductive data obtained from ad hoc commercial sampling off New South Wales ( NSW ). The egg surveys covered the known distribution of sardine off eastern Australia and included year‐round sampling in the northern and southern parts of this range. Egg distributions and analysis of gonadosomatic indices identified two spatio‐temporally separate spawning groups; one occurring off southern Queensland to northern NSW during late winter and early spring, and a smaller group off eastern Tasmania to southern NSW during summer. Most eggs were collected from waters 50–90 m deep, with sea surface temperatures of 18–23°C. Additive modelling indicated depth was the most significant factor driving selection of spawning habitat, followed by the interaction of month and latitude. Low egg densities were recorded in waters between 34–37°S, despite conditions within the ranges suitable for spawning. The presence of two spawning groups of sardine off eastern Australia supports recent findings that two sub‐populations occur in the region. Findings of this study will help to optimise the spatio‐temporal extent of future egg surveys and further confirm the need to coordinate future management of each sub‐population among relevant jurisdictions.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Blueprints of Effective Biodiversity and Conservation Knowledge Products That Support Marine Policy - Lauren V. Weatherdon; Ward Appeltans; Nadine Bowles-Newark; Thomas M. Brooks; Frances E. Davis; Katherine Despot-Belmonte; Stephen Fletcher; Cristina Garilao; Craig Hilton-Taylor; Tim Hirsch; Diego Juffe-Bignoli; Kristin Kaschner; et al. (Frontiers in Marine Science, 2017)

Integrated approach to determining stock structure: implications for fisheries management of sardine, Sardinops sagax, in Australian waters - Christopher Izzo; Tim M. Ward; Alex R. Ivey; Iain M. Suthers; John Stewart; Stuart C. Sexton; Bronwyn M. Gillanders (Reviews in Fish Biology and Fisheries, 2017)

Rapid assessment of fisheries species sensitivity to climate change - Gretta T. Pecl; Tim M. Ward; Zoë A. Doubleday; Steven Clarke; Jemery Day; Cameron Dixon; Stewart Frusher; Philip Gibbs; Alistair J. Hobday; Neil Hutchinson; Sarah Jennings; Keith Jones; et al. (Climatic Change, 2014)

Impacts of Drought, Flow Regime, and Fishing on the Fish Assemblage in Southern Australia’s Largest Temperate Estuary - Greg J. Ferguson; Tim M. Ward; Qifeng Ye; Michael C. Geddes; Bronwyn M. Gillanders (Estuaries and Coasts, 2013)

Pelagic ecology of a northern boundary current system: effects of upwelling on the production and distribution of sardine ( Sardinops sagax ), anchovy ( Engraulis australis ) and southern bluefin tuna ( Thunnus maccoyii ) in the Great Australian Bight - TIM M. WARD; LACHLAN J. MCLEAY; WETJENS F. DIMMLICH; PAUL J. ROGERS; SAM MCCLATCHIE; ROGER MATTHEWS; JOCHEN KÄMPF; PAUL D. VAN RUTH (Fisheries Oceanography, 2006)
Shelf waters of southern Australia support the world's only northern boundary current ecosystem. Although there are some indications of intense nitrate enrichment in the eastern Great Australian Bight (GAB) arising from upwelling of the Flinders Current, the biological consequences of these processes are poorly understood. We show that productivity in the eastern GAB is low during winter, but that coastal upwelling at several locations during the austral summer–autumn results in localized increases in surface chlorophyll a concentrations and downstream enhancement of zooplankton biomass. Sardine ( Sardinops sagax ) and anchovy ( Engraulis australis ) eggs and larvae are abundant and widely distributed in shelf waters of the eastern and central GAB during summer–autumn, with high densities of sardine eggs and larvae occurring in areas with high zooplankton biomass. Egg densities and distributions support previous evidence suggesting that the spawning biomass of sardine in the waters off South Australia is an order of magnitude higher than elsewhere in southern Australia. Sardine comprised >50% of the identified prey species of juvenile southern bluefin tuna (SBT, Thunnus maccoyii ) collected during this study. Other studies have shown that the lipid content of sardine from the GAB is relatively high during summer and autumn. We suggest that juvenile SBT migrate into the eastern and central GAB during each summer–autumn to access the high densities of lipid‐rich sardines that are available in the region during the upwelling period. Levels of primary, secondary and fish production in the eastern GAB during summer–autumn are higher than those recorded in other parts of Australia, and within the lower portion of ranges observed during upwelling events in the productive eastern boundary current systems off California, Peru and southern Africa.

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)